The impact of computer-assisted pronunciation on Saudi students’ production of English vowel sounds - Abdulmohsin A. Alshehri (Australian Journal of Applied Linguistics)
This study aimed to investigate the extent to which computer-assisted pronunciation (CAP) is influential in helping Hijazi students to develop their pronunciation of English vowels within a Saudi English as a foreign language (EFL) context. It also examined whether Saudi Hijazi learners taught English vowel sounds by CAP outperform those taught via hard-copy pronunciation materials. Data were collected from 18 students who undertook an English speaking course over 11 weeks. These learners were equally divided into the experimental and control groups, who received instruction on English vowels through CAP and traditional printed materials, respectively. Quantitative and qualitative methods were employed in this study. The results of the study show that CAP significantly enhanced Hijazi EFL students’ pronunciation of English vowel sounds, especially for those vowels that were nonexistent in their L1 phonemic inventory. They also suggest that CAP could be a beneficial tool to be incorporated into English speaking lessons.